ПРИВЛЕКАТЕЛЬНОСТЬ РЫНКА КАЗАХСТАНА ДЛЯ ИНВЕСТИЦИЙ - Калдияров, Д А (Journal of Economic Research & Business Administration, 2015)
This article is concerned with involving of foreign investments and makes it more comfortable.